2021
DOI: 10.4314/ovj.v11i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Low semen quality and adverse histological changes in testes of adult male mice treated with bee venom (Apis mellifera)

Abstract: Background: Male infertility has been on the rise since the past seven decades. Recently, in Libya, bee venom therapy (BVT) has become a popular method among alternative healthcare practitioners for treating male infertility. However, a literature search did not find any published studies that investigated the use of BVT for infertility treatment. Aim: To investigate the effect of bee venom on the male reproductive status through measurements of semen quality parameters and testicular histological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In contrast, BV might increase antioxidant enzyme activity and inhibit oxidation involved in scavenging the high level of ROS and improving the testicular alterations [47]. Furthermore, a study conducted by Regeai et al [48] showed the toxic and destructive effect of BV on testicular tissue; however, the study used normal animals and short duration. The results of this study highlighted the potential therapeutic effect of BV in male infertility.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, BV might increase antioxidant enzyme activity and inhibit oxidation involved in scavenging the high level of ROS and improving the testicular alterations [47]. Furthermore, a study conducted by Regeai et al [48] showed the toxic and destructive effect of BV on testicular tissue; however, the study used normal animals and short duration. The results of this study highlighted the potential therapeutic effect of BV in male infertility.…”
Section: Discussionmentioning
confidence: 98%
“…The previous study has determined the potential role of BV in ameliorating diabetic condition and their consequences. Only a single study assessed the adverse cytotoxic effect of BV on semen quality in healthy normal mice with a short duration of treatment [48]. In contrast, this study was conducted in alloxan-induced diabetic mice using two BV concentrations for 35 days.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility in men is triggered by changes in sperm quantity, movement, and/or shape that are found in collected samples. Recent research suggests that bee products may have preventative and therapeutic benefits for health, particularly infertility in men ( Regeai et al, 2021 ; Suleiman et al, 2021 ).…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Bee venom acupuncture is a highly effective method for the treatment of osteoarthritis and rheumatoid arthritis ( Hegazi, 2012 , Silva et al, 2015 , Abd El-Wahed et al, 2019 , Chen et al, 2020 ). In a recent study, it was proved that the treatment with bee venom results in reproductive disorders in the mouse model, such as reduction in sperm count, motility of sperm, testosterone level as well as some irregular structural changes in sperm morphology, seminiferous tubules ( Regeai et al, 2021 ). The aim of this study is to summarize the existing knowledge on BV with special emphasis on its various properties and therapeutic potential and suggest of new proposals for future research.…”
Section: Introductionmentioning
confidence: 99%